Utility of Immunofluorescence Antigen Mapping in Hereditary Epidermolysis Bullosa - Raghavendra Rao; Varsha M Shetty (Wolters Kluwer Medknow Publications, 2021)
Background: Epidermolysis bullosa (EB) is characterized by blisters and erosions on the trauma-prone areas of the body. It occurs as a result of mutation in the genes encoding structural proteins. Transmission electron microscopy (TEM) is considered the gold standard test in the laboratory diagnosis of EB. However, this test requires a lot of expertise and is not widely available. Immunofluorescence antigen mapping (IFM) is considered a suitable alternative with comparable sensitivity and specificity. However, there is paucity of studies analyzing the utility of IFM in the diagnosis of EB. Aims and Objectives: To study the utility of IFM in the laboratory diagnosis of EB. Materials and Methods: A cross-sectional study was conducted involving 179 biopsy specimens of patients with EB. IFM was carried out using a panel of monoclonal antibodies against K14, laminin 332, type IV collagen, and type VII collagen. Results: Diagnosis of EB simplex (EBS), junctional EB (JEB), and dystrophic EB (DEB) was made in 104, 28, and 26 biopsy specimens, respectively. The overall concordance rate was 41.3% with higher concordance rates in EBS. Conclusion: The present study is conducted to assess the efficacy of IFM in the diagnosis of EB with large sample size. Our study serves to establish IFM as an important tool in the diagnostic armamentarium of EB as the prognosis mainly rests on diagnosing the type of EB.